Religion and inequality in America research and theory on religion's role in stratification - Keister, Lisa A. 1968-; Sherkat, Darren E. 1965- (Cambridge University Press, 2014)
Despite the growing quantity and quality of research connecting religion to inequality, no single volume to date brings together key figures to discuss various components of this process. This volume aims to fill this gap with contributions from top scholars in the fields of religion and sociology. The essays in this volume provide important new details about how and why religion and inequality are related by focusing on new indicators of inequality and well-being, combining and studying mediating factors in new and informative ways, focusing on critical and often understudied groups, and exploring the changing relationship between religion and inequality over time.